1988
DOI: 10.1007/bf01655484
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls and progress in the management of abdominal aortic aneurysms

Abstract: Based on a review of the literature and 241 cases of abdominal aortic aneurysm (AAA) operated at the Mannheim Surgical Clinic, the progress and pitfalls in the management of this lesion are discussed. Progress in diagnosis is based on noninvasive imaging procedures, e.g., ultrasound, which lead to the detection of more aneurysms before they rupture. Ultrasound also plays a role in the observation of small asymptomatic aneurysms in high‐risk patients, helping some to avoid operation as well as rupture. Progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…If operations are staged, and tumor resection is performed first, delaying AAA treatment of a month, there is a potential for aneurysm rupture [5,6]. If AAA repair is performed first and tumor resection is delayed, there is a risk of local and metastatic spread of tumor, whereas there might be an overall increased operatory risk and an increased risk of bacterial graft contamination, if both procedures are simultaneously performed [7,8]. These general principles earn a different importance, according to the different biological and surgical characteristics of tumors that may be encountered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If operations are staged, and tumor resection is performed first, delaying AAA treatment of a month, there is a potential for aneurysm rupture [5,6]. If AAA repair is performed first and tumor resection is delayed, there is a risk of local and metastatic spread of tumor, whereas there might be an overall increased operatory risk and an increased risk of bacterial graft contamination, if both procedures are simultaneously performed [7,8]. These general principles earn a different importance, according to the different biological and surgical characteristics of tumors that may be encountered.…”
Section: Discussionmentioning
confidence: 99%
“…The reported experience, although it does not consider the option of endovascular treatment of AAA, which might be appealing in this setting, supports the simultaneous surgical treatment of AAA and several neoplasms. Such attitude spares the patient a second procedure, either abdominal [7,9] or endovascular. Although graft contamination is a real concern in a simultaneous procedure; to our knowledge, no graft sepsis related to such treatment has been reported up to now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 If AAA repair is performed and tumor resection is delayed, there is risk for interim spread of local and metastatic disease. 12,13 If the procedures are performed simultaneously, the risk of the surgery increases due to both the greater risk of bacterial graft contamination, higher blood loss, and possible stress on the patient due to a longer duration of surgery. These general principles may vary, depending upon the different characteristics of the malignancy that is encountered.…”
Section: Discussionmentioning
confidence: 99%
“…2,11 Endovascular AAA repair (EVAR) might lead to better results in the synchronous treatment of CRC and AAA, because it could minimize the risk of graft infection and shorten the period between AAA repair and CRC treatment. 1,[14][15][16][17][18][19] Considering the disparity in therapeutic strategies and the dearth of clear evidence, we conducted a systematic review of the literature and analyzed the reported cases of concomitant CRC and AAA management with a focus on the different treatment options and related therapeutic outcomes.…”
mentioning
confidence: 99%